A model-based approach for early robustness evaluation – Combination of Contact and Channel Approach with tolerance graphs in SysML - Horber, Dennis; Li, Jiahang; Grauberger, Patric; Schleich, Benjamin; Matthiesen, Sven; Wartzack, Sandro (Proceedings of the 33rd Symposium Design for X (DFX2022), 2022)
Considering variations is essential for the development of robust products, but the applicability of existing robust design approaches in early stages is challenging due to the lack of product information and high levels of abstraction. To overcome this, a combined model is presented, which enables a holistic robustness evaluation in a linked approach. This approach uses the contact and channel approach to identify the relations between embodiment and functions as well as the robustness evaluation based on tolerance graphs. The combined model is implemented with the Systems Modeling Language (SysML) and applied to a coining machine use case. An initial assessment of the model combination and a proposal for a methodically supported workflow for the holistic robustness evaluation is give
Keywords: Robust Design; Variation Management; Contact and Channel Approach; SysML; Model-based Development

A Model-Based Approach for Integrated Variation Management - Horber, Dennis; Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the ASME 2022 International Mechanical Engineering Congress and Exposition (IMECE2022), 2023)
Variation management is a responsible task for product developers, which have to balance the ever-increasing quality demands and cost pressures, while considering the product design as well as the manufacturing and assembly process. These aspects have a direct impact on its subsequent success in the market. Therefore, a large number of different activities of variation management are necessary. In this area, a wide variety of mostly document-centered methods support product developers, which have individual interfaces. Thus, it is currently not possible to map the entire variation management process in a single model. Especially with regard to the increasing availability of large amounts of data, the potential of an integrated variation management cannot be exploited efficiently. For this reason, this paper presents a novel model-based approach for the development of a combined system and tolerancing model. This model contains the processes and activities of integrated variation management and links them with further system models and the corresponding data. The presented approach is a superordinate model for variation management as well as its processes and provides the modeling of individual views of different stakeholders. In addition, process- and program-specific solutions can be integrated into the model, which enables a cross-linking of the data beyond their interfaces. In this paper, the approach is realized using the systems modeling language (SysML
Keywords: integrated variation management; model-based systems engineering; process modelling; change effects

Combining System Models and CAD for Change Scenario Management - Hick, Hannes; Schleich, Benjamin; Sanladerer, Stefan; Ryan, Karen; Trautner, Jessica; Piguet, Jean; Wilking, Fabian; Horber, Dennis; Faustmann, Clemens; Kranabitl, Philipp; Kollegger, Stefan; Bajzek, Matthias; et al. (33rd Annual INCOSE International Symposium, 2023)
In the development of complex mechatronic systems, interdisciplinary cooperation requires an exchange between stakeholders in order to ensure fulfillment of requirements and related functions. The cooperation of the stakeholders from different disciplines must be well coordinated to address systems changes. The system model as an essential aspect of model-based systems engineering, has to be linked to specific models of involved disciplines (mechanical, electrical/electronical and software) to enable a basis for automatic identification e.g., of affected subsystems and functions. This contribution discusses the potential of model linking from the perspective of change scenarios by considering published approaches to link system models and computer-aided design (CAD). A methodical approach on how descriptive system models can be used as base for computer-aided design is presented. This approach is analyzed by reviewing a use case for a design change scenario of an automotive eAxl
Keywords: MBSE

Conceptual Model for (Semi-) Automated Derivation of Evaluation Criteria in Requirements Modelling - Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2020)
Requirements act as a limitation of the solution space, which represents the stakeholders’ needs and guides the whole product development process. Therefore, forgotten requirements can lead to wrong decisions when using them as a basis for decision-making. This contribution introduces a novel approach to link the requirement and evaluation criteria models to address this problem. For setting up those criteria consistently, the requirements are classified using natural language processing and derived by a ruleset based on a developed mapping between requirement classes and criteria type
Keywords: requirements management; decision making; design evaluation; natural language processing

Digitale Durchgängigkeit im Toleranzmanagement am Beispiel der ganzheitlichen Robustheitsbewertung in frühen Phasen - Horber, Dennis; Brand, Otto; Li, Jiahang; Götz, Stefan; Matthiesen, Sven; Wartzack, Sandro (Tagungsband der 5. Summer School Toleranzmanagement 2023, 2023)

Durchgängige Systemmodellierung - Integration von Zielen in technische Systemmodelle im Kontext des Anforderungsmanagements - Horber, Dennis; Wilking, Fabian; Schleich, Benjamin; Wartzack, Sandro (Stuttgarter Symposium für Produktentwicklung SSP 2021, 2021)
Durch die steigende Komplexität technischer Konsumentenprodukte beschäftigen sich immer mehr Unternehmen mit Ansätzen, um diese Komplexität greifbarer zu machen. Ein Ansatz dafür ist das Model-Based Systems Engineering (MBSE). Ein zentrales Element dieses Ansatzes ist die Verwendung von Systemmodellen, die zur Beschreibung von Struktur und Verhalten des Systems dienen. Anforderungen lassen sich somit unmittelbar mit Systemelementen verbinden und verifizieren. Die im entwicklungsmethodischen Vorgehen oft vernachlässigten Ziele, die den Anforderungen hierarchisch übergeordnet sind, finden aber auch in diesen Modellen noch keine Anwendung. Dieser Beitrag beschäftigt sich damit, inwiefern sich Ziele konsistent in technische Systemmodelle integrieren lassen, sodass eine durchgängige Modellierung von den Zielen bis hin zu den einzelnen Elementen ermöglicht wird. Dabei werden bereits bestehende Möglichkeiten, hier beispielhaft in der System Modelling Language (SysML), um Systemelemente und Verbindungen ergänzt, um eine konsistente Integration von Zielen gewährleisten zu können und die Syntax der Notationen nicht erheblich zu beeinflussen.<br
Keywords: Model-Based Systems Engineering; MBSE; Systemmodell; Zielmodellierung; Anforderungsmanagement

Ein Klassifizierungssystem zur Anforderungssystematisierung - Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Design for X. Beiträge zum 30. DfX-Symposium, 2019)
This paper presents a holistic approach to structure and classify requirements of the product life cycle systematically and make them accessible for the evaluation process. In a first analysis step, process models of selected literature are analyzed regarding classification and structuring of requirements as well as their derivation into evaluation criteria. In a subsequent synthesis step, the classification system is developed with a consistent consideration of the multi-criteria evaluation process. This approach therefore contributes to raise the awareness of an appropriate handling of requirements and to minimize forgotten requirements as well as evaluation criteria. As a result, costly iterations in the development process can be reduced sustainably by using the proposed approac
Keywords: requirement engineering; requirement classification; multi criteria decision making; product development

Holistisches Toleranzmanagement am Lehrstuhl für Konstruktionstechnik - Wartzack, Sandro; Götz, Stefan; Bode, Christoph; Franz, Michael; Freitag, Stephan; Horber, Dennis; Kramer, Vincent; Roth, Martin; Schächtl, Paul (Tagungsband der 5. Summer School Toleranzmanagement 2023, 2023)

Identification of Property Change Impacts Based on Requirements-Oriented, Multi-Criteria Decision Models - Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2022)
As an outcome of the multi-criteria evaluation of different alternatives, product developers receive information on whether the evaluation alternatives meet the demanded property profile. If not, product characteristic and property changes are required, which can have desired and undesired effects. This contribution presents an MBSE-based approach, which extends the relational requirement model by value functions and product properties. Its novelty can be found in the integration of multi-criteria decision models, which are used to improve alternatives based on property change impact analyse
Keywords: decision making; requirements management; characteristics and properties; engineering change; model-based systems engineering (MBSE)

Interconnected Tolerancing Activities and the Role of Key Characteristics - Horber, Dennis; Götz, Stefan; Wartzack, Sandro (Research in Tolerancing, 2024)
Products are nowadays characterized by rising complexity, so that companies need to adapt their development processes to resulting challenges. Transferring this need for adaption to the tolerancing domain, new approaches are expected to enable companies to tackle increasing quality demands and costs pressures. Resulting from that, a variety of tolerancing activities exist, which are closely interconnected with the product development process. Their application leads to several artifacts, which can be gathered in a digital thread weaving through the processes. As most of these approaches are document-centered, new progresses in model-based systems engineering offer unused potential to ensure traceable processes. This chapter therefore presents an approach for the model-based formalization of tolerancing activities to contribute to this digital thread. Furthermore, a holistic approach for a common key characteristic model is described, which is used along with the formalized activities. Due to their importance for tolerancing, key characteristics are a profound basis for enabling traceability and the approach ensures a thorough link. It includes the systematic and automated derivation of key characteristics from requirements using natural language processing, their further extension and prioritization.<br

Investigating Modeling in Early Robust Design – A Study with the Modeling Method of Embodiment Function Relation and Tolerance Model - Li, Jiahang; Horber, Dennis; Renner, Philip; Jiajie, Yan; Götz, Stefan; Grauberger, Patric; Wartzack, Sandro; Matthiesen, Sven (Proceedings of NordDesign 2024, 2024)
Robust design (RD) aims to design systems that are insensitive to variation, reducing costly iterations in later product development stages. Evaluation of the early RD methods, often case-based like the modeling method with the EFRT model, lacks empirical investigation with novice applicants, which hinders further research into the success criteria of these methods. In this paper, a cross-over study evaluating the applicability and efficacy of the modeling method revealed its support for early RD. This encourages further RD research and provides a foundation for future investigatio
Keywords: Empirical Studies; Robust Design; Design Methods; Design Models

Natural Language Processing in Requirements Engineering and Its Challenges for Requirements Modelling in the Engineering Design Domain - van Remmen, Judith Sophie; Horber, Dennis; Lungu, Adriana; Chang, Fan; van Putten, Sebastiaan; Götz, Stefan; Wartzack, Sandro (Proceedings of the Design Society, 2023)
Requirements represent a central element in product development. The large number of requirements inevitably results in an increased susceptibility to errors, an expenditure of time and development costs. The associated problems motivate the application of Artificial Intelligence in the form of Natural Language Processing (NLP). In Requirements Engineering one main task is the classification of requirements which serves as the input in architectural models e.g. in SysML. In mechanical engineering there is still little overview regarding the interface between requirements classification and modelling. This paper provides an overview of the requirement classes and entities used in the literature and analyses their utilisation in modelling. Existing requirements classes usually do not offer the flexibility to be transferred to other domains. However, basic structures can be adopted from those classifications. This enables a clear assignment of existing classes to object classes in modelling. Resulting from the conducted literature study the observed predominant focus of research on the software industry requires an extension of the existing requirement classes and entities to enable further use and transfer to mechanical engineerin
Keywords: Requirements; Artificial intelligence; Natural Language Processing; Systems Engineering (SE); Literature review

Ontology-based knowledge provision for decision support in product development - Pickel, Jessica; Gerschütz, Benjamin; Horber, Dennis; Götz, Stefan; Wartzack, Sandro (Proceedings of the 34th Symposium Design for X (DFX2023), 2023)
The product development process confronts engineers with numerous decision problems. In this context, it is a challenge to consider all underlying heterogeneous data sources and decision methods to avoid incorrect decisions. Regarding these issues, ontologies offer the possibility to represent knowledge in a structured and adaptable way. Thus, this contribution proposes a methodical conception of a product development ontology and a novel approach to support developers in solving interrelated decision problems by providing relevant knowledge in a target-oriented way. In addition, the application is demonstrated by an exemplary development scenario for the axle design of a micromobility solutio
Keywords: Ontology; product development process; decision-making; requirements management; knowledge management

Potentiale von NLP-basierten Assistenzsystemen im Anforderungsmanagement - van Remmen, Judith Sophie; Horber, Dennis; Pickel, Jessica; Götz, Stefan; Wartzack, Sandro (Tagungsband zum Stuttgarter Symposium für Produktentwicklung SSP 2023, 2023)
Die Anwendung und Integration bestehender NLP-basierter Ansätze in das Anforderungsmanagement wird derzeit durch verschiedene Faktoren, darunter mangelndes Expertenwissen und Know-how, gehemmt. Motiviert durch das Fehlen einer Entscheidungshilfe für die Konzeptionierung NLP-basierter Assistenzsysteme fokussiert der vorliegende Beitrag die Entwicklung einer systematischen Handlungsempfehlung zur Potentialidentifikation und Risikominimierung. Die Entscheidungshilfe berücksichtigt dabei die Unternehmensdefinition hinsichtlich der Art des Unternehmens, dessen Produkttypologie und Referenzsysteme. Sie dient dazu, potentiell kritische Anforderungen zu identifizieren und daraus Voraussetzungen für die Umsetzung des NLP-unterstützten Soll-Prozesses abzuleiten. Die qualitative Anforderungs- erfüllung kann dabei als Indikator für das Potential oder Risiko in der Entscheidungsfindung genutzt werden. Diesbezüglich können bereits Herausforderungen für die eigene Implementierung des konzeptionierten Assistenzsystems oder die Beauftragung eines Softwarezulieferers abgeleitet und klar kommuniziert werden. Das entwickelte Konzept wird anhand eines akademischen Beispiels kritisch diskutier
Keywords: Natural Language Processing; Anforderungsmanagement; Digital Engineering

Procedure Model for Structured Relational Modeling of Requirements to Support Requirements-oriented Decision Making - Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2021)
The development of complex technical systems is characterized by a large number of system elements as well as their interactions. With regard to requirements management, many requirements have to be considered, which can have different relations to each other. If these requirements are used as basis for criteria in the decision making process, these relations must also be considered in the multi-criteria evaluation of product alternatives. Therefore, a computer-aided approach is presented in this paper, which allows the systematic modeling of requirement interactions focusing on multi-criteria decision making. For this purpose, basic relation types are identified, which are used to model submatrices in order to derive the Requirement Relation Matrix (RRM). Matrix-based as well as graph-based visualization methods are used for the RRM in order to improve the alternatives with the knowledge about the relational linkage. In addition, the effects of changes in requirements can be transferred to the decision making process. The approach is exemplarily applied to the extension of a test laboratory by a test benc
Keywords: Decision making; Requirements; Dependency; Graph visualization; Product modelling/models

Robust Conceptual Design for a Robust Early Embodiment Design - Horber, Dennis; Li, Jiahang; Grauberger, Patric; Götz, Stefan; Matthiesen, Sven; Wartzack, Sandro (Proceedings of NordDesign 2024, 2024)
Utilisation of Robust Design (RD) principles in early stages of product development can reduce costly iterations by identifying concepts that are less prone to functional losses caused by variations. Valuable implications can be drawn from those principles, which are currently not transferred to later stages. Motivated by that, the RD principles are studied with the EFRT-Model. The transferability of nine different RD principles to later stages is analysed with a variation simulation of the exemplary snap fit joint use case and discussed based on their utilisation on a four-point scal
Keywords: Robust Design; Simulation Based Design; Embodiment Design

Robustness evaluation in early phases of product development - Li, Jiahang; Horber, Dennis; Grauberger, Patric; Götz, Stefan; Wartzack, Sandro; Matthiesen, Sven (2023)

SIMULTANEOUS DEFINITION OF KEY CHARACTERISTICS IN ORDER TO FACILITATE ROBUST DESIGN IN EARLY PRODUCT DEVELOPMENT STAGES - Götz, Stefan; Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2021)
The success of complex product development projects strongly depends on the clear definition of target factors that allow a reliable statement about the fulfilment of the product requirements. In the context of tolerancing and robust design, Key Characteristics (KCs) have been established for this purpose and form the basis for all downstream activities. In order to integrate the activities related to the KC definition into product development as early as possible, the often vaguely formulated requirements must be translated into quantifiable KCs. However, this is primarily a manual process, so the results strongly depend on the experience of the design engineer. In order to overcome this problem, a novel computer-aided approach is presented, which automatically derives associated functions and KCs already during the definition of product requirements. The approach uses natural language processing and formalized design knowledge to extract and provide implicit information from the requirements. This leads to a clear definition of the requirements and KCs and thus creates a founded basis for robustness evaluation at the beginning of the concept design stage. The approach is exemplarily applied to a window lifter.
Keywords: Robust design; Conceptual design; Requirements; Early design phases

Supporting early robust design for different levels of specific design knowledge – An adaptive method for modeling with the Embodiment Function Relation and Tolerancing model - Li, Jiahang; Horber, Dennis; Grauberger, Patric; Götz, Stefan; Wartzack, Sandro; Matthiesen, Sven (Design Science, 2024)
Early robust design can lead to significant cost savings in the later stages of product development. In order to design systems that are insensitive to various sources of deviation in the early stages, specific design knowledge (SDK) plays a crucial role. Different design situations result in higher or lower levels of derivable SDK, which leads to different activities to achieve the development goal. Until now, no method has been developed to consider the different levels of derivable SDK from various design situations for early robustness evaluation. To address the problem, this paper outlines an adaptive modeling method using the Embodiment Function Relation and Tolerance (EFRT) model. The method is developed in two contrasting design situations, each with a high and low level of derivable SDK, and evaluated in another two corresponding case studies. It has a consistent structure with five stages and gates. At each stage, the derivable SDK is taken into account and the individual modeling steps are adapted. This method provides design engineers with concrete support for early robustness evaluation of a product concept in different development scenario
Keywords: design methods; product development; robustness evaluation; design situation; design knowledge

The balance between a usable and emotional product design – a comparison of different methods for prioritising relevant influencing factors - van Remmen, Judith Sophie; Horber, Dennis; Händel, Jonas; Miehling, Jörg; Wartzack, Sandro (DESIGN 2024, 2024)
Designing an equally usable and emotionally appealing product remains a challenge for product developers, not least due to conflicting goals. Product developers need to constantly map the affective user requirements to the product, whereby the requirements for the emotional and usable product design often cannot be equally addressed. The systematic approach presented can help product developers in conflicting decision-making situations to represent these affective user requirements by selecting and prioritising context-relevant influencing factors using multi-criteria decision-making methods.<br
Keywords: user-centred design; emotional engineering; user experience; decision making

The Balance Between a Usable and Emotional Product Design - A Concept for Prioritising Relevant Influencing Factors - van Remmen, Judith Sophie; Horber, Dennis; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 34th Symposium Design for X (DFX2023), 2023)
Usability and emotionality represent fundamental aspects of user experience. Yet designing an equally usable and emotionally appealing product remains a challenge for product developers, not least due to conflicting goals. Product developers need a deep understanding of what is important to users in different situations of use to make a user-oriented decision between a more usable or emotionally appealing product design. To support product developers in conflicting decision-making situations, the presented systematic approach for the selection and prioritization of context-relevant influencing factors can contribute. By mapping influencing factors and the prioritization using decision theory methods, the importance of the influencing factors in different usage scenarios can be identifie
Keywords: Usability; emotional design; user experience; user-centred design; decision making

Tolerancing in product design – a holistic description scheme - Götz, Stefan; Roth, Martin; Schächtl, Paul; Kramer, Vincent; Bode, Christoph; Horber, Dennis; Franz, Michael; Freitag, Stephan; Miehling, Jörg; Wartzack, Sandro (Design Science, 2025)
Along with increasing product complexity and quality requirements, the consistent consideration of inevitable production-induced variations within the product development process becomes a decisive factor for the market success of products. Consequently, various tolerancing approaches have emerged over the last few decades. However, tolerancing is considered complex in education, research, and industry, as it is a highly interdisciplinary task that takes place at different levels of detail, ranging from Robust Design to tolerance specification to manufacturing process design. This contribution proposes a novel approach that allows a holistic and structured description of tolerancing and fosters a common understanding among all involved stakeholders from design, manufacturing, and inspection. This is achieved by categorizing it into several distinct elements: activities, methods, tools, models and data, information, and knowledge. This ensures clarity and supports the utilization of existing approaches. While this contribution focuses on tolerancing in product design, the linkage to subsequent product realization stages and further engineering domains is also addressed in the proposed description scheme. An exemplary classification of research papers and a description of a practical development process of a technical system with its different tolerancing activities illustrate the benefits of the proposed description schem
Keywords: Tolerancing; Dimensional Management; Variation Management; Robust Design; Product Design

Utilization of MBSE Models for a Micro-Mobility Solution in the Context of System of Systems - Wilking, Fabian; Horber, Dennis; Schleifer, Simon; Behringer, Marc; Miehling, Jörg; Götz, Stefan; Wartzack, Sandro (2024 19th Annual System of Systems Engineering Conference (SoSE), 2024)
The adoption of Model-Based Systems Engineering (MBSE) methodologies, particularly employing system models such as those represented by SysML diagrams, holds significant promise in comprehending the intricacies inherent in the development of technical systems. However, a thorough evaluation of the advantages of MBSE is imperative to rationalize the implementation endeavors associated with MBSE methodologies. With the Utilization of system models, the concept of using system models in different application scenarios apart from the initial model purpose as well as other lifecycle stages is feasible. In the realm of System of Systems (SoS), where the complexity is notably elevated, it is fundamental to generate comprehensive models that elucidate the interdependencies among systems. This undertaking necessitates an extension of the conventional Utilization of system models with an adaptation to the unique challenges presented by SoS. This research introduces an approach that extends the Utilization of system models to SoS-models, elucidating feasible scenarios.<br
Keywords: Model-Based Systems Engineering; MBSE; System of Systems; SysML; Mobility

Utilization of system models in model-based systems engineering: definition, classes and research directions based on a systematic literature review - Wilking, Fabian; Horber, Dennis; Götz, Stefan; Wartzack, Sandro (Design Science, 2024)
The use of system models within model-based systems engineering (MBSE) is essential for improved communication or system documentation. Previous publications have investi- gated further reuse of these system models, for example, transforming them directly into discipline-specific models for reuse. The authors refer to this as the term “Utilization” of system models. It aims the compensation of modelling efforts and a further integration of linked models within MBSE. Motivated by a lack of common understanding of this term, a systematic literature review of the state of the art is presented. With this systematic overview, a definition and classification system for different use cases and system life cycle stages are created. These are key results to support engineers and researchers in adopting existing or discovering new utilization approaches. This supports the mission of advanced systems engineering and aims the identification of new research directions coming along with SysML v2 and the advanced systems engineering methods.
Keywords: Model-based systems engineering; MBSE; Systems engineering; System models; SysML

Utilizing System Models for Multicriteria Decision-Making - A Systematic Literature Review on the Current State of the Art - Horber, Dennis; Pickel, Jessica; Götz, Stefan; Wartzack, Sandro (IEEE Open Journal of Systems Engineering, 2024)
The rising system complexity of modern products requires new approaches within model-based systems engineering to manage the upcoming challenges. System development is characterized by a wide variety of decisions to be made. These situations have to be modeled within a holistic system model to ensure traceability. Motivated by lack of a comprehensive overview of approaches, this paper presents the results of a systematic literature study focusing on utilizing system models in decision-making. By that, the existing gap between theoretical foundations and implementation in practical use is intended to be closed through providing practitioners insights to relevant approaches. Apart from that, researchers are enabled to derive new research directions from the corpus of literature. Relevant reports use different diagrams to model a decision situation or its processes and reuse those diagrams as well as their contents to feed methods from multi-criteria decision-making. By that, new objectives are added to those diagrams, namely to enable extensive decision-making, which is understood as their utilization. Thus, this paper provides an overview of applied decision-making approaches, languages used to model the decision context and the use of external tools, where the decision-making algorithms are executed. The findings show that the majority of existing approaches only cover certain aspects of the decision-making situation in the system model and especially the formalization of the decision-making process is hardly considered. Besides that, future research fields including the analysis of potentials coming along with the introduction of SysML v2 and especially its API are identifie
Keywords: decision-making; model-based systems engineering (MBSE); multi-criteria decision-making (MCDM); product development

Utilizing the Embodiment Function Relation and Tolerance Model for Robust Concept Design - Li, Jiahang; Horber, Dennis; Keller, Christoph; Grauberger, Patric; Götz, Stefan; Wartzack, Sandro; Matthiesen, Sven (Proceedings of the Design Society, 2023)
The early use of Robust Design (RD) supports the development of product concepts with low sensitivity to variation, which offers advantages for reducing the risk of costly iterations. Due to the lack of approaches for early evaluation of product robustness, the embodiment-function-relation and tolerance (EFRT-) model was developed, which combines the contact and channel approach and tolerance graphs. The information exchange of both approaches offers a high potential for reliable robustness evaluation results. However, that potential currently relies unused, since the link between applicable robustness criteria and the extended information is missing. To solve this problem, four research steps were determined: (1) understanding of robustness, (2) collection of RD principles, (3) identification of EFRT-model information and (4) mapping of RD principles and information. The results show nine adapted RD principles, the identified model information for the robustness evaluation, the evaluation criteria as well as their mapping. Utilizing the mapping and the proposed criteria in this contribution, a more comprehensive robustness evaluation in early stages is enable
Keywords: Robust Design; Conceptual Design; Product Modelling / Models; Variation Management; Contact and Channel Approach